Genetic Diversity and Characteristics of blaNDM-Positive Plasmids in Escherichia coli - Zhang, Zhiren; Guo, Hengzhao; Li, Xiaodong; Li, Wenting; Yang, Guang; Ni, Wenjun; Zhan, Meixiao; Lu, Ligong; Zhang, Zhenlin; Li, Xiaobin; Zhou, Zhiling (Frontiers in Microbiology, 2021)
New Delhi metallo-β-lactamases (NDMs), including at least 24 variants, are a rapidly emerging family of β-lactamases worldwide, with a variety of infections caused by NDM-positive strains usually associated with very poor prognosis and high mortality. NDMs are the most prevalent carbapenemase genes in Escherichia coli worldwide, especially in China. The vast majority of blaNDM cases occur on plasmids, which play a vital role in the dissemination of blaNDM. To systematically explore the relationships between plasmids and blaNDM genes in E. coli and obtain an overall picture of the conjugative and mobilizable blaNDM-positive plasmids, we analyzed the variants of blaNDM, replicon types, phylogenetic patterns, conjugative transfer modules, host STs, and geographical distributions of 114 blaNDM-positive plasmids, which were selected from 3786 plasmids from 1346 complete whole genomes of E. coli from the GenBank database. We also established links among the characteristics of blaNDM-positive plasmids in E. coli. Eight variants of blaNDM were found among the 114 blaNDM-positive plasmids, with blaNDM-5 and blaNDM-1 being the most dominant. The variant blaNDM-5 was mainly carried by the IncX3 plasmids and IncF plasmids, which were regarded as the most common conjugative plasmids in the blaNDM-5-positive plasmids in E. coli. IncC plasmids were observed to be the predominant carriers of blaNDM-1 genes in E. coli, which are the most common conjugative plasmids in the blaNDM-5-positive plasmids in E. coli. Other blaNDM-1-carrying plasmids also included IncM2, IncN2, and IncHI1. Three blaNDM-4-positive plasmids with IncFIA(HI1) replicon from E. coli ST405 were found to be the potential mobilizable plasmids. The overall picture of the conjugative and mobilizable blaNDM-positive plasmids in E. coli was described in our study.